OP0242 Health-related quality of life improved only slightly although disease activity decreased over 3 years in early axial spondyloarthritis: 442 patients from the desir cohort. (15th June 2017) - Puyraimond-Zemmour, D; Desthieux, C; Ruyssen-Witrand, A; Fautrel, B; Gossec, L
Abstract : Background: Current guidelines emphasize Health-related Quality of life (HRQoL) as a priority in health care but the link with disease activity is incomplete. Objectives: The objective was to describe in patients with early axial spondyloarthritis (axSpA) the evolution of SF36 and of ASDAS-CRP over a 3 years follow up. Methods: DESIR is an ongoing prospective, multicenter, longitudinal, observational French cohort (1). Patients had inflammatory back pain of more than 3 months and less than 3 years suggestive of axSpA. For our analysis, only patients with no missing data for MCS and PCS SF36 values during the first 3 years were included. HRQoL was assessed by the SF36 questionnaire and its 2 subscales (scored 0–100 with higher scores indicating better status): the physical composite score (PCS) including physical function, physical role, bodily pain and general health (GH) and the mental composite score (MCS) including mental health (MH), emotional role, social function and vitality. Disease activity was assessed by the ASDAS-CRP. Each outcome was assessed at baseline, 6 months, 12 months, 24 months and 36 months. The mean and median outcomes were calculated at each time-point and comparisons used ANOVA on repeated data. Baseline predictive factors associated with worse SF36 scores (lower half of mean values over 3 years) were identified by univariate then multivariate logistic regression, among the baseline variables age, gender, educational level, work status, smoking, HLAB27, radiological sacroiliitis, extra-articular manifestations (uveitis, psoriasis, inflammatory bowel disease) and ASDAS-CRP. Results: In all, 442 patients were analyzed: at baseline, mean age was 34.2±8.6 years; mean disease duration was 18.6±10.7 months; 239 (54%) were females, 274 (62%) had HLAB27 and 124 (28%) had radiological sacroiliitis. At baseline, mean PCS, MCS and ASDAS-CRP were respectively 40.5±9.2, 40.4±11.0 and 2.6±1.0. Over 3 years, although mean ASDAS-CRP improved, HRQoL improved only slightly (Figure). All the SF36 subdomains improved (all p<0.001), though GH and MH improved less (data not shown). In univariate analysis, lower educational level, not being in a white collar job, younger age and higher ASDAS-CRP were significantly associated to lower HRQoL over 3 years. In multivariate analysis, only higher baseline ASDAS-CRP (odds ratio=0.49 [95% confidence interval 0.29; 0.79]) was associated to lower HRQoL. Conclusions: In early axSpA, HRQoL was affected similarly for the physical and mental components and only slightly improved over 3 years. In contrast, ASDAS-CRP improved substantially. However, ASDAS-CRP was a stronger driver of HRQoL than demographic characteristics. The drivers of HRQoL in inflammatory rheumatic disorders should be further explored. References: Dougados M. et al. Clinical presentation of patients suffering from recent onset chronic inflammatory back pain suggestive of spondyloarthritis: The DESIR cohort.Joint Bone Spine, 2015;82(5):345–51. Disclosure of Interest: None declared